2019
DOI: 10.1111/ecog.04562
|View full text |Cite
|
Sign up to set email alerts
|

Soil biota composition and the performance of a noxious weed across its invaded range

Abstract: The success of invasive plant species is driven, in part, by feedback with soil ecosystems. Yet, how variation in belowground communities across latitudinal gradients affects invader distributions remains poorly understood. To determine the effect of soil communities on the performance of the noxious weed Cirsium arvense across its invaded range, we grew seedlings for 40 days in soils collected across a 699 km linear distance from both inside and outside established populations. We also described the mesofauna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…4). These bacteria have also been widely reported in the invasion areas of other alien plants, including Japanese barberry, Acacia dealbata and Cirsium arvense (Kamutando et al 2017;Coats et al 2014;Nunes et al 2019). Proteobacteria were the most dominant bacterial groups in this study, con rmed that Proteobacteria are the dominant bacterial community in terrestrial soil ecosystem (Bazylinski et al 2013).…”
Section: Discussionsupporting
confidence: 76%
“…4). These bacteria have also been widely reported in the invasion areas of other alien plants, including Japanese barberry, Acacia dealbata and Cirsium arvense (Kamutando et al 2017;Coats et al 2014;Nunes et al 2019). Proteobacteria were the most dominant bacterial groups in this study, con rmed that Proteobacteria are the dominant bacterial community in terrestrial soil ecosystem (Bazylinski et al 2013).…”
Section: Discussionsupporting
confidence: 76%
“…However, many plant-associated microbes were enriched in rhizospheres both in the pot experiment and the invaded site, and these genera were generally higher in the invaded field than those in the pot experiment, indicating their important roles in the natural environment. The interactions between an invasive plant and associated soil communities changed across the invaded range (Nunes et al, 2019). In our study, we found that there is a difference of M. micrantha rhizosphere between the pot experiment and the field site.…”
Section: Discussionmentioning
confidence: 53%
“…There is increasing evidence that belowground enemies can be as important for species co-existence and community dynamics as aboveground enemies [62] and may even drive the positive biodiversity-productivity relationships in native plant communities [63]. Nevertheless, surprisingly few studies have looked on enemy release from belowground enemies [52,64] and most of them concentrated on plant-soil feedback (e.g., [65][66][67][68][69][70][71][72]. These studies frequently demonstrated that release from soil-borne pathogens may favor plant invasions [52,64], but the role of belowground insect herbivory is still insufficiently understood and studied.…”
Section: Discussionmentioning
confidence: 99%